Design of Earthquake Resistant Buildings : Useful Guidelines - Prasad, Mahesh (AMC Indian Journal of Civil Engineering, 2023)
Incidents of earthquake of severe intensity are in news every now and then in various parts of world. In the recent past, Turkey witnessed a severe earthquake suffering loss of life and damage of buildings and public properties. India also bears severe risk for seismic tremors as almost 58% of the total area falls in active seismic zones. According to the latest seismic zone data published, Zones 2,3,4 and 5 are the active seismic zones where structures should be invariably designed considering Earthquake loads (EL) apart from normal loads like Dead load (DL), Imposed load (IL), Wind load (WL), Snow load , and Accidental loads as applicable. In cities, the practice of multi-storey buildings and high rise buildings is picking up very fast. Earthquake failures in buildings never remain confined to its built up area alone, rather it adversely affects the safety of buildings in its near vicinity by pounding effect. Therefore, future constructions in vulnerable cities must be subjected to certain statutory bindings to follow norms for Earthquake Resistant Designs as applicable for the seismic zones in a particular city/town. For High Importance Factor buildings like hospitals, nursing homes, schools /colleges, office buildings /administrative buildings, the design norms still become inescapable. With pace of growth in economy, construction activities are likely to zoom in almost all states and major cities and towns. Therefore, it is high time that Earthquake Resistant Design norms are publicised and strictly enforced in letter and spirit. Earthquake resistant design needs certain general tips like symmetry in construction, avoiding practice of floating columns in super structure, placing heavy loads on roof like water tanks without well designed supporting structure for resisting lateral forces, practice of stilt floors at ground level, providing Soft Storeys at intermediate floors which are more vulnerable to earthquake induced lateral shear. The concept of shear walls has been found to be quite effective in resisting lateral shear induced by high intensity earthquake forces. Shear walls in longitudinal as well as transverse directions, symmetrically placed in plan can prove to be a boon in facing multidirectional lateral forces generated by earthquake tremors. The only watchword in shear wall concept is that it must start at foundation level well tied up and run right up to the roof level and remain well integrated with moment resisting RC frame of the building. The next important aspect in earthquake resistant design is a careful and thorough soil exploration to determine the most suitable foundation option. The soil characteristics, sandy and high water table may cause Liquefaction, which is dangerous for safety of buildings. In such adverse situation, it is desirable to lay deeper foundation or substitute sandy strata with granular material. Pile foundation in such cases can be a safe option. Concept of Base Isolation and use of damping devices are other options to keep the building structure safe from seismic tremors. Use of elastomeric pads, rollers at foundation base of column footings helps in absorbing the energy generated by seismic tremors by damping devices/pads. The super structure of the building remains unaffected by earthquake forces. Such measures involve higher cost but can be cost effective in case of important functional buildings like hospitals, office complex, and industrial buildings.